Using Technology to Enhance Feedback to Student Teachers. (May 2016) - Gibson, Lenwood; Musti-Rao, Shobana
The importance of effective and efficient feedback is paramount during the student teaching experience. This experience is a vital component of many teacher preparation programs. During these limited experiences, supervisors deliver performance feedback that is designed to improve the way student teachers implement evidence-based practices and/or adhere to treatment protocol, also known as treatment fidelity. Improving fidelity is very important to the success of preservice teachers and the children in their classrooms. This column outlines and discusses the use of technology in the preservice teacher supervision process. Four separate technologies are described and suggestions for utilizing them to deliver effective feedback are provided.